Progress in the Application and Research of Magnetic Field-Assisted Low-Temperature Storage Technology for Foods - WENG Jintong, SHENG Qinghai, LIU Jingke, ZHANG Xiaodi, LIU Junli, ZHANG Aixia, LI Pengliang, ZHAO Wei (Shipin Kexue, 2023)
With the continuous development of science and technology, the conventional low-temperature storage technology can no longer meet people’s pursuit of food quality. In recent years, magnetic fields have been widely used in the field of low-temperature food storage due to its advantages of being simple, efficient, safe, pollution-free and energy-saving. Magnetic fields can maintain the eating quality of stored food by optimizing the cooling and freezing process, regulating enzyme activity and reducing microbial contents. In order to provide a theoretical reference for the industrial application of magnetic fields in low-temperature storage of foods, this paper reviews the mechanism of magnetic field-assisted low-temperature storage technology and its application in various kinds of food, summarizes shortcomings in this field, and gives an outlook on future directions of development.